PERAN GREENPEACE DALAM MENANGANI KERUSAKAN HUTAN AKIBAT DEFORESTASI DI INDONESIA PADA MASA MORATORIUM HUTAN - Widri Khairani; Irwan Iskandar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The Indonesian government has a Forest Moratorium policy that has been in effect since 2011. However, until the moratorium policy was made permanent in 2019, deforestation still occurred in Indonesia, including in areas protected by the moratorium. To understand how an international non-governmental organization Greenpeace has played a role in dealing with forest destruction due to deforestation in Indonesia. Based on the theory of the role of international organizations at the level of group analysis with descriptive qualitative research methods, using primary data obtained through interviews, the official website of Greenpeace and related Ministries as well as secondary data from books, journals, and reports related to forest destruction in Indonesia. The results showed that in dealing with forest damage due to deforestation during the forest moratorium, Greenpeace actively carried out direct forest campaigns on the Mata Harimau Tour in Sumatra and Kalimantan collecting data on the moratorium on forests damaged by deforestation, campaigning online through websites and social media, and opening forest data. the moratorium is reduced due to deforestation, meet with relevant parties to influence the implementation of the moratorium policy so that zero deforestation is realized in Indonesia..Keywords : Forest Moratorium policy, Greenpeace, Deforestation